Thermal Chemically Deposited Zno Nanostructures: Influence of Post-Deposition Annealing Temperature on Ph Sensor Performance - Bazilah, Aimi; Awang, Zaiki; Sobihana Shariffudin, Shafinaz; Hana Herman, Sukreen (International Journal of Engineering and Technology, 2018)
Zinc oxide (ZnO) nanostructures were synthesized via thermal chemical deposition (TCVD) method and applied as the sensing membrane of an extended-gate field effect transistor (EGFET) pH sensor.Â The ZnO nanostructures undergone a post-deposition heat treatment with the temperature ranging from 200-500 Â°C for 15 min in air ambient. The influence of the post-deposition heat treatment on the physical and pH sensing characteristics was investigated. The FESEM images showed that the surface morphology of the samples were dependent on post-annealing treatment. The as-deposited sample showed the biggest grain size and non-uniformed structures. Applying the post-annealing heat treatment caused the surface morphology to become denser and uniform. The most ideal temperature for the heat treatment for EGFET pH sensor application was found at 300 Â°C resulting in a pH sensitivity of 48.2 mV/pH with 0.9646 linearity.Â Â Â